Analisis Potensi Energi Surya Untuk Alat Bioteknologi Penghasil Nata De Coco Dengan Memanfaatkan Limbah Air Kelapa - Dion Brian Hatimanis; Stieven N. Rumokoy; Christopel H. Simanjuntak; Maureen Langie; Daisy D. G. Pangemanan; Herotje Siwi; Fridly Manawan (Jurusan Teknik Elektro - Politeknik Negeri Manado, 2024)
Coconut water (Cocos nucifera. L) has the potential to become a useful nata de coco product by utilizing biotechnology tools. Research conducted on